Implementasi Sistem Manajemen Keselamatan Sebagai Standar Keselamatan Pelayanan Lalu Lintas Udara - SISILIA, YUANNA (UI Scholars Hub, 2011)
This research aimed to explain how PT (Persero) Angkasa Pura II (PT AP II) maintained safety management system while fulfilling its role as an aviation service provider, and what problems occurs in its implementation. The researcher tried to find out relationship between the concepts of safety management system, conducted by ICAO (International Civil Aviation Organization), with its daily practices. This research used positivism approach. The data were collected through in-depth interviews with Eight Head Office Officials of PT AP II. PT AP II is forced to provide a user-oriented-aviation-service, while fulfilling international standards set by ICAO. As a result PT AP II encountered many difficulties in fulfilling ICAO’s target to conduct a perfect safety management system in 2009. These difficulties impeded the implementation of safety management system from coping with international standards or any other necessary standards